Necrotizing Erythema Nodosum Leprosum (ENL) Post-MDT in Multibacillary Hansen’s Disease: A Case Report - Rahma, Mira Nupila; Susana, Made Prajnana Adhi Parasikan; Muhtaram, Wibisono Hasanul; Fadlila, Ashila Sallama Nur; Tiffani, Indri; Mubarak, Lalu Abdul; Utami, Retno Dwi; Isqie, Baiq Mayada; Gunawan, Florentcia Davina; Astika, Nensy Dwi; Oka, Pande Komang Inten Widya Iswara; Kurniati, Kurniati; Hapsari, Yunita (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Necrotic erythema nodosum leprosum (ENL) is a rare and severe type 2 leprosy reaction that mainly affects patients with multibacillary Hansen's disease and may progress to tissue necrosis. We report the case of a 26-year-old woman with released-from-treatment (RFT) multibacillary Hansen's disease who presented with recurrent painful erythematous nodules, cutaneous necrosis, paresthesia, numbness, and peripheral neuropathy. Clinical examination revealed enlarged and tender peripheral nerves with sensory and motor impairment, while slit-skin smear demonstrated a bacteriological index of +3. Laboratory findings showed leukocytosis, neutrophilia, and mild microcytic anemia, indicating an active inflammatory process. The patient was diagnosed with recurrent necrotic ENL after completion of multidrug therapy and was treated with systemic corticosteroids, analgesics, wound care, emollients, neurotropic supplementation, and iron therapy. Clinical improvement and a reduction in the bacteriological index were observed during follow-up, although recurrent skin lesions and residual sensory neuropathy persisted. This case emphasizes that necrotic ENL may occur after RFT and highlights the importance of early recognition, appropriate treatment, and close follow-up to reduce recurrence, prevent irreversible nerve damage, and improve long-term outcomes.